2018
DOI: 10.1186/s40168-018-0536-y
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose degradation at the holobiont level: teamwork in a keystone soil invertebrate

Abstract: BackgroundWoodlice are recognized as keystone species in terrestrial ecosystems due to their role in the decomposition of organic matter. Thus, they contribute to lignocellulose degradation and nutrient cycling in the environment together with other macroarthropods. Lignocellulose is the main component of plants and is composed of cellulose, lignin and hemicellulose. Its digestion requires the action of multiple Carbohydrate-Active enZymes (called CAZymes), typically acting together as a cocktail with compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 116 publications
(130 reference statements)
4
100
4
3
Order By: Relevance
“…There is increasing evidence that the gut microbial community of animals is involved in a wide range of processes in the host, including health, grow and development as well as behaviour; it can even affect the nervous system by secreting metabolites [1][2][3][4][5][6][7][8][9][10][11]. These microbes can also assist in energy uptake and metabolism [12,13]. Previous research has demonstrated that ruminants depend heavily on gut microbiota to digest fibre in the rumen and use products such as short-chain fatty acids (SCFAs) to meet their energy needs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that the gut microbial community of animals is involved in a wide range of processes in the host, including health, grow and development as well as behaviour; it can even affect the nervous system by secreting metabolites [1][2][3][4][5][6][7][8][9][10][11]. These microbes can also assist in energy uptake and metabolism [12,13]. Previous research has demonstrated that ruminants depend heavily on gut microbiota to digest fibre in the rumen and use products such as short-chain fatty acids (SCFAs) to meet their energy needs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The organic carbon within wood in the form of lignocellulose is accessible to mixotrophic and heterotrophic lignocellulose degraders (i.e. Proteobacteria and Bacteroidetes 51,52 ), thereby the organic carbon could act as an environmental filter. Inert substrates (i.e.…”
Section: Substrate Differences Drive Early Compositionmentioning
confidence: 99%
“…These microbiotas can also assist in the whole-body energy harvest [12]. For example, previous research has demonstrated ruminants depend heavily on gut microbiota to digest fiber in rumen, and panda without a rumen also relys on it's microbiome to degrade hemicellulose and starch in bamboo to provide themselves with energy [13][14][15][16]. The functions of gut microbiota are mainly determined by their composition which is affected by many factors of the host, such as genetic background, health condition, environmental differences, and even social behavior [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%